A new species of Callyntra (Coleoptera: Tenebrionidae) from central Chile - Zúñiga-Reinoso, Álvaro; Cid-Arcos, Mauricio (Zootaxa, 2015)
Callyntra Solier, 1836 is a genus mainly from Chile, with one species occurring in Argentina, which currently contains 20 described species. Recent explorations in the Andes Mountain Range in Chile, have resulted in the collection of specimens morphologically different from all previously described species. The aim of this paper is to describe a new species of Callyntra, discuss its relationship with other species in the genus, and highlight sexual dimorphism and potential conservation status.